Seasonal Variations in Habitat Use are Associated With Food Availability Changes in Assamese Macaques (Macaca assamensis) Inhabiting Limestone Forest - Fengxiang Mo; Guanghua Liu; Ailong Wang; Shengyuan Liu; Shixin Nong; Kechu Zhang; Zhonghao Huang (Ecology and Evolution)
ABSTRACT Data on habitat use of wild animals facilitate conservation management and further our understanding of their environmental adaptations. We collected data on the habitat utilization of 16 groups of Assamese macaques (Macaca assamensis) in the limestone forests in Guangxi, China, to explore the pattern and seasonality of habitat use of these macaques. Our results showed that cliffs were the most frequently used hill parts by the macaques, followed by flat zones, hillsides, and hilltops. The cliffs were the most frequently used during resting and moving, whereas the hillsides and flat zones were used as the main feeding sites. Patterns of habitat use seasonally varied. Specifically, the utilization frequency of the cliff was lower in the rainy season than in the dry season. Besides, feeding occurred more frequently on hillsides and flat zones. The dietary composition of the Assamese macaques affected the use of hill parts, indicating that the consumption of young leaves was positively correlated with the use of cliffs and was passively related to the use of hillsides. Moreover, ecological factors had impacts on habitat use. The use of hilltops and cliffs increased whereas the utilization of hillsides and flat zones decreased with the day length and temperature dropping. The availability of flower and fruit were also key ecological factors affecting habitat utilization. We conclude that the dietary composition, day length, flower availability, and fruit availability are determinants of habitat utilization for Assamese macaques, highlighting the importance of ecological factors in shaping their behavioral adaptation to the unique limestone forests.